Histopathological and Biomedical Parameters Determination in the Protective Effect of Hydroalcoholic Extract of Allium Jesdianum on Hepatotoxicity Induced by Bromobenzene: Effect of Allium Jesdianum Extract on Bromobenzene Induced Hepatotoxicity - Kalantari, Heybatullah; Shamsi Ehsan, Tahereh; Samimi, Azin; Kheradmand, Parvin; Shirani, Maryam; Zeidooni, Leila (Iranian Journal of Pharmaceutical Sciences, 2018)
Allium Jesdianum (AJ) is the native plant mostly grown in Middle East region that has the excellent pharmacological properties. In this study, we evaluated the hepatoprotective effect of hydroalcoholic extract of AJ on liver injury induced by Bromobenzene (BB) in male mice. Animals were randomly divided into five groups, control group received normal saline plus olive oil, groups 2-4 received (500, 1000 and 2000 mg/kg) AJ extract plus BB for 5 days and 5th group received BB (460 mg/kg). On the fifth day all groups received hexobarbital sodium (25 mg/kg, i.p). It should be noted that sleeping time of the all mice were recorded. After 24 hours the mice were sacrificed. By serum and tissue biomarkers such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), reduced glutathione (GSH), malondialdehyde (MDA), and histopathological studies were measured. The results showed that BB significantly increased sleeping time, ALT, AST, and MDA levels besides and decreased GSH level compared with the control group. AJ extract at doses1000and 2000 mg/kg showed a significant alter in all studied endpoints and dose 2000 mg/kg showed a marked improvement in histopathological examination. The present finding indicated that administration of the hydroalcoholic extract of AJ could prevent hepatotoxicity induced by BB via improvement serum and tissue parameters and histopathological alterations in liver tissue.